The Analysis of Investment Interests of Millennial Generation in Batam City with Planned Behavior Theory - Cuandra, Fendy (2020)
The purpose was to study the factors of attitudes, subjective norms, financial self-efficacy, financial knowledge, and personality traits of young investors towards investment intentions (The Planned Behaviour Theory). The research method used is causal comparative research with the sudents pupolation in Batam City within the age range of 20-34 years. There is moderating and two mediations variable used to analyse whether the variable is related to investment intentions. The results showed that the variable financial knowledge mediated by attitude affects directly towards investment intentions. The variable personality traits of investors mediated by financial independence have indirect effect on investment intentions. In addition, risk taking indicators on investor personality traits moderate affect the overall financial self-efficacy on investment intentions in millennials. Positive significance also occurs in investor personality variables on financial knowledge whereas the variable Theory of Planned Behaviour (TPB) on investment intentions has a significant effect only on the variable such as attitude and subjective norms. The financial self-efficacy variable on investment intentions is not significant to the millennial.